The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1007/s00192-013-2280-y
|View full text |Cite
|
Sign up to set email alerts
|

Does fibromyalgia influence symptom bother from pelvic organ prolapse?

Abstract: In women with symptomatic prolapse, fibromyalgia is associated with an increased risk of levator myalgia and 50% more symptom bother from pelvic floor disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 16 publications
1
22
1
Order By: Relevance
“…In the study conducted by Jones et al, the total PFDI‐20 score in 177 patients with fibromyalgia was slightly higher (159 ± 55) than the total scores reported by our sample of patients with fibromyalgia (143 ± 5.7), with the greatest contribution to the total distress originating from the colorectal‐anal symptoms followed by genital prolapse and urinary symptoms . In another study, patients with genital prolapse symptomatology who self‐reported fibromyalgia scored a total of 145 ± 63 on the PFDI‐20 and 105 ± 84 on the PFIQ‐7 which were significantly higher compared to subjects reporting genital prolapse symptoms but not fibromyalgia . These results confirm the greater impact and severity of PFD when comorbid fibromyalgia is present.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In the study conducted by Jones et al, the total PFDI‐20 score in 177 patients with fibromyalgia was slightly higher (159 ± 55) than the total scores reported by our sample of patients with fibromyalgia (143 ± 5.7), with the greatest contribution to the total distress originating from the colorectal‐anal symptoms followed by genital prolapse and urinary symptoms . In another study, patients with genital prolapse symptomatology who self‐reported fibromyalgia scored a total of 145 ± 63 on the PFDI‐20 and 105 ± 84 on the PFIQ‐7 which were significantly higher compared to subjects reporting genital prolapse symptoms but not fibromyalgia . These results confirm the greater impact and severity of PFD when comorbid fibromyalgia is present.…”
Section: Discussioncontrasting
confidence: 55%
“…11 The potential association between fibromyalgia and PFD is supported by several studies. [12][13][14] Patients with fibromyalgia were shown to experience bothersome urinary tract symptoms and higher prevalence of pelvic organ prolapse, defecatory dysfunction, and sexual dysfunction compared to controls. 12,13 Additionally, history of fibromyalgia diagnosis was found to be relatively elevated among women who were referred to urogynecology clinic assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, patients’ FM was severe enough that it had been evaluated at least once in a rheumatology practice. Lastly, we did not complete physical examinations on our patients, thus we cannot replicate Adams’ findings of levator myalgia (Adams et al, 2014) or determine its correlates.…”
Section: Discussionmentioning
confidence: 88%
“…Newly published data report that women with FM have 50% greater pelvic floor symptoms compared with matched women without FM who were evaluated at a urogynecology clinic for pelvic floor distress (Adams et al, 2014). The women with FM had significantly worse pelvic floor distress than age-matched women without FM (PFDI scores 145.0 [63.3] versus 110.5 [64.5; p = .005]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation